2004
DOI: 10.1002/jcb.20038
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a stable cell line to evaluate cellular Runx2 activity

Abstract: Runx2 is an essential transcription factor for osteoblast differentiation from early commitment step to final differentiation. Based on its crucial role in osteoblast differentiation, the transcriptional activity of Runx2 protein implies more valuable information for osteoblast differentiation than any other parameters, such as Runx2 mRNA or protein level. Thus, a sensitive, specific, and consistent method to determine the Runx2 transcriptional activity has long been expected. Here we suggest a stable cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…We previously reported that phosphorylation (Kim et al, 2003; Kim et al, 2004) and subsequent protein stabilization of Runx2 (Park et al, 2010) is required for its transactivation activity for the stimulation of osteoblast differentiation. As a matter of fact, it was reported that the genetic insufficiency of Runx2 could be overcome by osteoblast-specific overexpression of constitutively active MEK1 (MEK1-Ca) and could be exaggerated by the expression of dominant-negative MEK1 (Ge et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that phosphorylation (Kim et al, 2003; Kim et al, 2004) and subsequent protein stabilization of Runx2 (Park et al, 2010) is required for its transactivation activity for the stimulation of osteoblast differentiation. As a matter of fact, it was reported that the genetic insufficiency of Runx2 could be overcome by osteoblast-specific overexpression of constitutively active MEK1 (MEK1-Ca) and could be exaggerated by the expression of dominant-negative MEK1 (Ge et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…[16] To see if the Runx2 promoter responded to SAHA, a transient reporter assay was conducted by using 6XOSE as previously described. [14] As shown in Figure 1, luciferase activity was generated in a dose-dependent manner, with maximal activity seen with 10 µM SAHA. The EC50 was calculated as 1.0 µM.…”
Section: Resultsmentioning
confidence: 99%
“…[14] The cells were treated with SAHA at the indicated concentrations with FGF-2 as a control at 24 hr after transfection. Luciferase activity was measured by using the dual-luciferase assay system (Promega, Madison, WI, USA) in a Dynex luminometer.…”
Section: Methodsmentioning
confidence: 99%
“…As described previously (Kim et al ., ; Kim and Kim, ), the p6 × osteoblast‐specific cis‐acting element (OSE) 2‐luc reporter vector was used for measuring runt‐related transcription factor 2 (Runx2) activity. Briefly, it was transiently transfected into C2C12 cells (4 × 10 3 cells/well) cultured in a 96‐well plate for 24 h. Then, the culture medium was changed with DMEM‐containing 5% FBS, and cells were treated with SCE.…”
Section: Methodsmentioning
confidence: 99%